Hak Cipta sebagai Objek Jaminan Fidusia dalam Perjanjian Kredit Perbankan di Indonesia - Ertananda, Annisa; Yetniwati, Yetniwati; Suryahartati, Dwi (Recital Review, 2025)
This research aims to examine the implementation of Article 16 paragraph (3) of Law No. 28 of 2014 on Copyright, which states that copyright can be used as an object of fiduciary security. The research addresses two main issues: How is the regulation of copyright valuation (as an intangible asset) arranged for its use as fiduciary collateral in bank credit distribution in Indonesia? And does the Fiduciary Security Law provide opportunities for copyright to be used as collateral in credit agreements? To analyze the objectives of this thesis, a normative juridical method was employed. The approach is based on primary legal materials, including Law No. 42 of 1999 on Fiduciary Security, Law No. 28 of 2014 on Copyright, and Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 on Banking. The findings indicate that, normatively, copyright fulfills the requirements to be used as an object of fiduciary collateral because it is an intangible asset that is transferable and holds economic value. However, its implementation within the banking system still faces obstacles, particularly in the areas of valuation and acceptance by financial institutions. Therefore, a more structured valuation standard and synergy among relevant institutions are needed to optimize the use of copyright as a legitimate and productive collateral instrument within the national financing system.